Preparasi Katalis CaO/Fly Ash Dan Penggunaannya Pada Reaksi Transesterifikasi Minyak Sawit Off Grade Untuk Produksi Biodiesel - Anggraini, Diva Putri; Helwani, Zuchra; Saputra, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Calcium oxide preparation of solid base catalyst through calcination, hydration, dehydration methods with fly ash to load calcium oxide through impregnation method. Effect of dehydration temperature and time on the catalytic performance were studied. The catalyst with the highest activity is obtained when the dehydration temperature of 600 Â°C and the dehydration time of 3 hours with transesterification reaction conditions of a molar ratio of methanol/oil 6:1, catalyst dosage of 6% by weight, temperature of 70 Â°C for 2 hours with yield biodiesel results reached 84,32%. CaO, SiO, Ca2SiO4 and Ca(OH)2 materials was found in the catalyst through x-ray diffraction (XRD) analysis with a catalyst alkalinity values of H_ > 9.3 through alkalinity analysis using hammet indicator phenolphthalein and specific surface area of catalyst is 8,31 m2/g through Brunauer-Emmett-Teller (BET) analysis. Some methyl ester such as methyl palmitate and methyl oleate was found in the biodiesel through Gas Chromatography-Mass Spectrometry (GC-MS) analysis.Keywords: biodiesel, calcination, dehydration, hydration, transesterification